Fecal Microbiota Transplantation Shows Marked Shifts in the Multi-Omic Profiles of Porcine Post-weaning Diarrhea - Su, Yuan; Li, Xiaolei; Li, Diyan; Sun, Jing (Frontiers in Microbiology, 2021)
Weaning is the most critical phase in pig production and is generally associated with significant impacts on intestinal morphology, structure, physiology, and immune responses, which can lead to subsequent production inefficiencies such as decreases in growth and intake and increases in morbidity and mortality. In the present study, we attempted to explore the effects of fecal microbiota transplantation (FMT) on the fecal microbiota, fecal metabolites and transcriptome in the jejunum, colon, liver, spleen and oral mucosa in piglets with post-weaning diarrhea and to evaluate the therapeutic potential of FMT in piglets with post-weaning diarrhea. We found that FMT partially relieved the symptoms of diarrhea in piglets, and microbiota analysis results indicated that unclassified_f_Prevotellaceae was identified as an FMT-associated bacterial family at 66 d and that the Shannon index in the healthy group at 34, 38, and 66 days were higher than that at 21 d. Functional enrichment analysis of the oral mucosa, liver, jejunum and colon showed that most of the differentially expressed genes (DEGs) were enriched in the terms metabolic process, immune response, and inflammatory response. Moreover, the enriched fecal metabolites focused mostly on apoptosis, beta-alanine metabolism, glutathione metabolism, and sphingolipid metabolism. We tried to detect specific ‘metabolite-bacterium’ pairs, such as ‘g_Catenisphaera-stigmastentriol’, ‘p_Bacteroidetes-(6beta,22E)-6-hydroxystigmasta-4,22-dien-3-one’ and ‘g_Prevotellaceae_NK3B31_group-stenocereol’. Overall, the present study provides a theoretical basis for the alleviation of weaning stress and contributes to the realization of effective and sustainable application of FMT in the pig production industry in the future.